Cathodic corrosion protection systems : a guide for oil and gas industries - Bahadori, Alireza (Elsevier, 2014)
Corrosion is a naturally occurring cost, worth billions in the oil and gas sector. New regulations, stiffer penalties for non-compliance and aging assets are all leading companies to develop new technology, procedures and bigger budgets catering to one prevailing method of prevention, cathodic protection. Cathodic Corrosion Protection Systems: A Guide for Oil and Gas Industries trains on all the necessary reports, inspection criteria, corrective measures and critical standards needed on various oil and gas equipment, structures, tanks, and pipelines.